Contrastive Analysis Of Subordinate Clause As Adjective In English Novel And Indonesian Novel - Salwa Nabila (Universitas Muhammadiyah Sumatera Utara, 2021)
This research dealt with contrastive analysis that is Adjective Clause in Complex Sentence in English Novel and Indonesian Novel that is Harry Potter and the Goblet of the Fire and its Indonesian Version. The objective were to find out the similarities and differences between English and Bahasa Indonesia subordinate clause as adjective in English novel and Indonesian novel. The researcher focused on the complex sentence (68 sentences) which have adjective marks (that, who, which, who, whom, whose) and analyzed the kinds of the complex sentence and the sentence structure to find the contrast of the two languages. The theory used was Quirk and Greenbaum about basic sentence structure in English and Noortyani about basic sentence structure in Bahasa Indonesia. According to Quirk and Greenbaum there were seven kinds of basic sentence structures: SubjectVerb-Adverb, Subject-Verb-Complement, Subject-Verb-Object, Subject-VerbObject-Adverb, Subject-Verb-Object-Complement, Subject-Verb-Object-Object, Subject-Verb. But according to Noortyani (2017) there was only one basic sentence structure Subjek-Predikat-Objek-Keterangan in Bahasa Indonesia. Contrastive analysis was used to analyzed the data from the novel Harry Potter and the Goblet of Fire, both English and Indonesian version which was published in 2005. The data showed that from 37 chapters, the research was found that only 44 clauses had subordinate adjective clauses. 27 of them were similar in English and in Bahasa Indonesia, and the rest 17 of them were different in English and Bahasa Indonesia. It was found that English and Bahasa Indonesia had similar basic sentence structure but there were some conditions that make them contrast. Keyword: Contrastive Analysis, Subordinate Clause as Adjective, English and Indonesian Novel